Thermal analysis of an enriched flame incinerator for aqueous residues - Lacava, P. T.; Carvalho, J. A.; Pimenta, A. P.; Ferreira, M. A. (Elsevier B.V., 2006)
The use of oxygen to enrich the combustion air can be an attractive technique to increase capacity of an incinerator originally designed to operate with air, If incinerator parameters such as operation temperature, turbulence level and residence time are fixed for a certain fuel supply rate, it is possible to increase the residue consumption rate using enriched air. This paper presents the thermal analysis for operation with enriched air of an aqueous residue experimental incinerator. The auxiliary fuel was diesel oil. The theoretical results showed that there is a considerable increase in the incineration ratio up to approximately 50% of O-2 in the oxidiser. The tendency was confirmed experimentally. Thermal analysis was demonstrated to be an important tool to predict possible incinerator capacity increase. (C) 2005 Published by Elsevier Ltd.